Qual o olhar da escola para a dança? - Sass, Stephanie de Oliveira [UNESP] (2016)
The dance is present in human history. From ancient civilizations, many dances have served and still serve as a characteristic of certain peoples and regions of the world. But the dance goes way beyond something cultural, it is also a way that individuals found to express the various emotions without words were necessary. Thinking about the importance of dance and how it remains present in our society, the school would be the ideal place to learn to dance and enjoy its benefits. We know that the Law of Guidelines and Bases 9394/96 ensures the Art education - means Music, Theatre, Visual Arts and Dance - and the following year the National Curriculum Parameters were available that have a book to deal specifically about Art education; then the present work aims to research and answer these questions: How is the dance education within the school environment? Teachers are receiving proper training?And what teachers are responsible for teaching dance? The school environment is prepared for the teaching of dance and this is a very distant reality yet? For better understanding of the subject, a qualitative survey was conducted from the literature review and specific legislation. I conclude that the teaching of dance evolved historically managed their space within the school, but unfortunately the law is not enough to ensure teaching in blows. We believe that subjectivity is a problem with regard to teaching, and many aspects need to be deepened and other questions should be asked to discuss the topic dance in education